Comparison of ovulation inducers in an FTAI programme with sexed semen in Bos taurus x Bos indicus heifers - Toro García, Diana Carolina (2021)
The aim of this study was to compare the efficiency of estradiol cypionate (ECP) and estradiol benzoate (EB) as ovulation inducers in a fixed-time artificial insemination program (FTAI) using sexed semen in Senepol x Brahman red heifers. All animals received on day 0 an intravaginal device of progesterone (P4) of 0.5 g for eight days + 2 mg BE. Heifers in group 1 (n=177) received 150 μg PGF2α + 150 IU eCG + 1 mg CPE and heifers in group 2 (n=177) 150 IU eCG + 150 μg PGF2α and 24 h later received 1 mg BE. Heifers were inseminated with sexed semen 60 h after removal of the P4 device. The diameter of the preovulatory follicle and the gestation rates were determined by type of ovulation inducer. The diameter of the preovulatory follicle in heifers treated with ECP (11.48 ± 2.88 mm) was statistically similar to those treated with BE (10.81 ± 2.08 mm). A higher gestation rate (p=0.0069) was found in the ECP group (51.4%) than in the BE group (38.4%). It is concluded that CEP in comparison with BE as an ovulation inducer in IATF protocols favors pre-ovulatory follicle growth and gestation rates.